IS THERE A “LOW INTEREST RATE TRAP”? - Li, Kui-Wai (Ekonomika, 2012)
This article stylizes the monetary policy features applied during the chairmanship of Mr. Alan Greenspan and condenses statistical discussion into the “low interest rate trap” in the U.S. economy. Data from the U.S. in the decade prior to the 2008 financial crisis are used. A monetarist solution to the “low interest rate trap” is provided. The paper challenges the theoretical discussion on the Keynes’ interest rate – output relationship, and poses the question whether difference in investment returns would present a different picture in output growth.